BTLA-Expressing Dendritic Cells in Patients With Tuberculosis Exhibit Reduced Production of IL-12/IFN-α and Increased Production of IL-4 and TGF-β, Favoring Th2 and Foxp3+ Treg Polarization - Zhang, Jun-Ai; Lu, Yuan-Bin; Wang, Wan-Dang; Liu, Gan-Bin; Chen, Chen; Shen, Ling; Luo, Hou-Long; Xu, Huan; Peng, Ying; Luo, Hong; Huang, Gui-Xian; Wu, Du-Du; et al. (Frontiers in Immunology, 2020)
Little is known about how tuberculosis (TB) impairs dendritic cell (DC) function and anti-TB immune responses. We previously showed that the B and T lymphocyte attenuator (BTLA), an immune inhibitory receptor, is involved in TB pathogenesis. Here, we examined whether BTLA expression in TB affects phenotypic and functional aspects of DCs. Active TB patients exhibited higher expression of BTLA in myeloid dendritic cells (mDCs) and plasmacytoid DCs (pDCs) subsets compared with healthy controls (HCs). BTLA expression was similarly high in untreated TB, TB relapse, and sputum-bacillus positive TB, but anti-TB therapy reduced TB-driven increases in frequencies of BTLA+ DCs. BTLA+ DCs in active TB showed decreased expression of the DC maturation marker CD83, with an increased expression of CCR7 in mDCs. BTLA+ DCs in active TB displayed a decreased ability to express HLA-DR and to uptake foreign antigen, with a reduced expression of the co-stimulatory molecule CD80, but not CD86. Functionally, BTLA+ DCs in active TB showed a decreased production of IL-12 and IFN-α as well as a reduced ability to stimulate allogeneic T-cell proliferative responses. BTLA+ mDCs produced larger amounts of IL-4 and TGF-β than BTLA- mDCs in both HCs and APT patients. BTLA+ DCs from active TB patients showed a reduced ability to stimulate Mtb antigen-driven Th17 and Th22 polarizations as compared to those from HCs. Conversely, these BTLA+ DCs more readily promoted the differentiation of T regulatory cells (Treg) and Th2 than those from HCs. These findings suggest that TB-driven BTLA expression in DCs impairs the expression of functional DC surrogate markers and suppress the ability of DCs to induce anti-TB Th17 and Th22 response while promoting Th2 and Foxp3+ Tregs. Keywords: tuberculosis; B and T lymphocyte attenuator; dendritic cells; CD83; CCR7; HLA-DR; CD80; CD86; IL-12; IFN-α; stimulatory function.